Using IOT Technologies by Medical Staff for Their Patients - Dragos Nicolae Nicolau; Alin Zamfiroiu (Communications of International Proceedings, 2020)
As we all know, health is the most precious gift in the life of every human being, but it must be permanently preserved and protected and which once lost is difficult to recover. But this can be easily avoided or remedied, as medicine jumps to our aid. Medicine is the branch of biological sciences that aims to analyze the human body and find solutions to diseases that can affect people's lives. In recent years, the spread and diversification of sensors and devices with the ability to connect to the Internet and beyond, have led to the transformation of the Internet of Things (IoT) into an essential component in most areas and also in the eHealth domain. This paper aims to address the subject of the Internet of Health Things (IoHT) and to provide an overview of its applicability as a substitute for permanent care by a knowledgeable patient. In the future, a fairly significant evolution of technology in the medical field is expected, as much better applications will appear than those already on the market, applications that will be very helpful to both doctors and nurses, one of which is the one that allows remote patient monitoring.
Keywords: IOT; medical; healthcare; patients; solution; eHealth.